Financial Literacy of Pre-Service Economics Teachers in Indonesia - Muhamad Supian; Ribut Wahyu Eriyanti (Lembaga Yasin AlSys, 2026)
Financial literacy has become a core competence in the digital economy, particularly for pre-service teachers who are expected to model and transmit sound financial practices to future generations, yet empirical evidence continues to show a persistent gap between awareness and actual competence among university students. This study aims to examine the multidimensional financial literacy profiles of pre-service economics teachers in Indonesia and to identify implications for teacher education in digitally mediated contexts. A quantitative descriptive survey design was employed, involving 100 pre-service economics teachers selected through purposive sampling. Data were collected using a validated questionnaire measuring financial knowledge, financial behaviour, and financial attitudes, and were analysed using descriptive statistics and Pearson correlation in SPSS 26. The findings reveal two central paradoxes: high awareness of financial literacy is not accompanied by adequate financial knowledge, and extensive engagement with digital financial services does not correspond with a sound understanding of financial risk. Participants demonstrated moderately positive financial attitudes and high levels of digital financial usage, yet exhibited low-to-moderate financial knowledge and inconsistent long-term financial behaviour. These results contribute to the theoretical development of multidimensional financial literacy by positioning it as a pedagogical competence in teacher education and highlight the misalignment between digital financial engagement and substantive financial capability. The study concludes that pre-service economics teachers require applied, reflective, and digitally grounded financial literacy learning experiences, and recommends curriculum redesign in teacher education programs to integrate case-based learning, digital finance simulations, and reflective practices, thereby strengthening future teachers’ readiness to deliver credible and effective financial education.